Analysis of Service Quality on Subscription Decisions with Customer Satisfaction as a Mediation Variable (Survey on the Community of Sukabumi City Users of IndiHome Internet Services) - Nurul Fitriani; Erry Sunarya; Kokom Komariah (LP2M IAIN Palopo, 2025)
This study aims to analyze the Influence of Service Quality on IndiHome Internet Service Subscription Decisions with Customer Satisfaction as a mediating variable. The existence of customer complaints indicates that the rate of subscription decisions is very low. The research method used was a survey with a questionnaire distributed to 135 users of IndiHome internet service in Sukabumi City. The data obtained was analyzed using path analysis to test between the variables studied. The results of this study show that Service Quality has a significant effect on Customer Satisfaction, and Customer Satisfaction has a positive and significant effect on subscription decisions, In addition, Customer Satisfaction is proven to play a mediating variable that strengthens the relationship between Service Quality and Subscription Decisions. These findings indicate that the better the quality of service provided, the more likely customers are to feel satisfied, and that satisfaction ultimately strengthens the Subscription Decision. This research provides insights for companies to continuously improve the quality of services provided through customer satisfaction to maintain subscription decisions.